Chemical Characteristics of Snack bar from Grain Germinated Rice Flour with Added Penja Fish Flour - Azis, Nur Afni; Safarni, Rizka Aulia; Fathanah, Nurul (Jurnal Biologi Tropis, 2025)
: This study aimed to evaluate the chemical characteristics of snack bars formulated from grain germinated rice flour combined with penja fish (Sicyopterus spp.) flour as a potential local protein rich ingredient. The experiment employed a Completely Randomized Design (CRD) with two formulations: P0 (100% germinated rice flour : 0% penja flour) and P1 (80% germinated rice flour : 20% penja flour). Chemical analyses included moisture content, ash, protein, carbohydrate, and total energy. The results showed that the addition of 20% penja flour significantly affected (p<0.05) all chemical parameters. Treatment P1 exhibited the highest values of ash (1.82%), protein (34.65%), carbohydrate (11.06%), and total energy (437.5 kcal/100 g), while reducing moisture content to 14.51%. The increase in nutritional value was attributed to the high protein content of penja fish and the nutrient contribution from germinated rice flour. These findings indicate that combining germinated rice flour and penja fish flour has strong potential for producing nutrient dense local snack bars.